Banana marketing performance in Blantyre Agricultural Development Division, Malawi - Ndengu, Joseph D., author (Colorado State University. Libraries, 1990)
This study provides insight into the complexities underlying the marketing of bananas in Blantyre Agricultural Development Division (A.D.D.), in southern Malawi. While farmers formed the core of the study, varying numbers of wholesalers/dealers, retailers and truckers were also contacted. A dualistic system of marketing operated in the area; that is, farmers sold their bananas both directly to consumers and also through middlemen. Sales, in order of importance based on patronage, were directly to the urban markets by the farmers themselves, to the middlemen/traders, to the village or roadside markets and lastly to the local markets. The most important problem was that of transportation, especially in getting the bananas to the urban markets. The main issue was the condition of the outlet road system. It appears that there is a lot of risk taking on the part of the truckers who opt to operate in the area. A detailed market performance analysis was not possible due to the paucity of relevant data. However, imperfect indicators of performance were highlighted. These included physical losses as bananas passed through various channels; price setting by market authorities; erratic supplies and inconsistent volume measures. Retail prices for a period of 69 days showed highly significant differences among mean prices of the three grades of bananas - large, medium and small. There appeared to be no relationship at all between the price movements for the large and medium size bananas. However, those for large and small, as well as medium and small, showed considerably higher degrees of positive association.
Keywords: Produce trade -- Malawi; Produce trade -- Developing countries; Farm produce -- Marketing; Bananas -- Malawi -- Marketing